Retesting the hypothesis that early Diphtheria-Tetanus-Pertussis vaccination increases female mortality: An observational study within a randomised trial. Issue 11 (8th March 2022) - Sørensen, Marcus Kjær; Schaltz-Buchholzer, Frederik; Jensen, Andreas Møller; Nielsen, Sebastian; Monteiro, Ivan; Aaby, Peter; Benn, Christine Stabell
Highlights: Healthier infants were more likely to receive early-DTP before 2 months of age. Receiving early-DTP had no effects on all-cause mortality in the present study. Receiving early-DTP after BCG-at-birth tended to increase female mortality. Co-administration of BCG and DTP tended to reduce all-cause mortality. Routine vaccinations and campaigns may affect the non-specific effects of vaccines. Abstract: Background: There are worrying indications that diphtheria-tetanus-pertussis (DTP) vaccine has negative non-specific effects for females. We previously found, in a trial of early-Bacillus Calmette-Guérin (BCG) to low weight (LW) neonates, that receiving early-DTP (before 2 months of age), was associated with increased female mortality compared with no-DTP/delayed-DTP. Within a subsequent LW trial, we aimed to retest this observation. Methods: Between 2010 and 2014, in Guinea-Bissau, 2, 398 infants were randomised 1:1 to early-BCG (intervention) or delayed-BCG (standard practice for LW neonates) and visited at 2, 6 and 12 months of age to assess nutritional and vaccination status. DTP is recommended at 6 weeks of age. We examined the effect of having "early-DTP" versus "no-DTP" at the time of the 2-month visit on all-cause mortality between the 2- and 6-month visits in Cox models stratified by sex and adjusted for BCG-group and 2-month-weight-for-age (z-scores) providing adjusted mortality rate ratios (aMRRs). We analysed to which extent conditions varied between the present and the previous LW trials and how that might have affected the overall result of comparing the early-DTP and the no-DTP groups. Results: At the time of the 2-month visit, 75% (1, 795/2, 398) had received DTP. Those vaccinated had better anthropometric indices than no-DTP infants at birth and by 2 months of age. Between the 2- and 6-month visits, 29 deaths occurred. The early-DTP/no-DTP aMRR was 1.09 (95% CI: 0.44–2.69); 1.19 (0.45–3.15) for females and 0.77 (0.14–4.19) for males. Compared to the previous study, the present study cohort had 56% (30–72%) lower overall mortality, fewer no-DTP infants, higher BCG vaccination coverage and several more oral polio vaccine campaigns. Conclusion: We did not find that early-DTP was associated with increased female mortality as found in a previous study; differences in results may partly be due to a decline in overall mortality and changes in vaccination practices.